Crystallization of struvite in the presence of calcium ions: Change in reaction rate, morphology and chemical composition. Issue 1 (31st December 2022) - Perwitasari, D. S.; Muryanto, S.; Jamari, J.; Bayuseno, A. P.
Abstract: Ammonium, phosphorus, and potassium from wastewater treatment with a coexisting ion of calcium may be recovered simultaneously through struvite and struvite-(K) crystallization. This paper presents the quantitative assessment of the impact of calcium ions on the kinetics and crystallization of those crystals. Initial solutions containing dose levels of Ca 2+ ion and pH 9 were set up for experiments in a stirred laboratory crystallization at ambient temperature. According to the pH reduction data, the observed precipitation kinetics followed in two steps; the first step (0–3 min) and the second step (3–60 min) in which linear regression analysis of both kinetic data fit with first-order rate constants. In the absence of calcium, the computed kinetic constants are respectively 2.568 h −1 for the first stage and 1.548 h −1 for the second stage. The kinetic rate constants followed with the increased dose of Ca (Ca/Mg > 0.5), which lengthened the crystallization of multiphase crystallization of Mg and Ca-phosphates. Accordingly, calcium had a negative effect on the morphology, purity, and quantity of the final crystalline product. This quantitative understanding of how calcium affects the crystallization of struvite and struvite-(K) reliably improves knowledge about controlling the quantity of wastewater recovery products.